Field‐aligned currents in Saturn's southern nightside magnetosphere: Subcorotation and planetary period oscillation components. Issue 12 (16th December 2014) - Hunt, G. J.; Cowley, S. W. H.; Provan, G.; Bunce, E. J.; Alexeev, I. I.; Belenkaya, E. S.; Kalegaev, V. V.; Dougherty, M. K.; Coates, A. J.
Abstract We investigate magnetic data showing the presence of field‐aligned magnetosphere‐ionosphere coupling currents on 31 Cassini passes across Saturn's southern postmidnight auroral region. The currents are strongly modulated in magnitude, form, and position by the phase of the southern planetary period oscillations (PPOs). PPO‐independent currents are separated from PPO‐related currents using the antisymmetry of the latter with respect to PPO phase. PPO‐independent downward currents ~1.1 MA per radian of azimuth flow over the polar open field region indicative of significant plasma subcorotation are enhanced in an outer plasma sheet layer of elevated ionospheric conductivity carrying ~0.8 MA rad−1 and close principally in an upward directed current sheet at ~17°–19° ionospheric colatitude carrying ~2.3 MA rad−1 that maps to the outer hot plasma region in Saturn's magnetosphere (equatorial range ~11–16 Saturn radii (RS)) colocated with the UV oval. Subsidiary downward and upward currents ~0.5 MA rad−1 lie at ~19°–20.5° colatitude mapping to the inner hot plasma region, but no comparable currents are detected at larger colatitudes mapping to the cool plasma regime inside ~8 RS. PPO‐related currents at ~17.5°–20° colatitude overlap the main upward and subsidiary downward currents and carry comparable rotating upward and downward currents peaking at ~1.7 MA rad−1. The overall current layer colatitude is also modulated with 1° amplitude in the PPO cycle, maximum equatorward adjacent to the peak upward PPO current and maximum poleward adjacent to peak downward PPO current. This phasing requires the current system to be driven from the planetary atmosphere rather than directly from the magnetosphere.